Gut-brain-liver axis in growth hormone deficiency: role of microbiota-derived short-chain fatty acids in ethnic variability and therapeutic development - Meng, Dongming; Kong, Wei; Cheng, Sai; Liu, Hua; Huang, Congfu (Frontiers in Public Health, 2025)
Growth hormone deficiency (GHD) is a pediatric endocrine disorder characterized by dysregulated growth hormone/insulin-like growth factor-1 (GH/IGF-1) axis activity and gut microbiota imbalance. Emerging evidence highlights the gut-brain-liver axis as a critical modulator of growth, with microbiota-derived short-chain fatty acids (SCFAs) playing dual roles in GH suppression and IGF-1 enhancement. This review synthesizes preclinical and clinical data to address ethnic variability in microbiota composition and therapeutic challenges. Key findings reveal that Chinese GHD cohorts exhibit reduced Bifidobacterium and fecal butyrate, whereas Spanish cohorts show minimal differences, potentially due to dietary fiber intake (e.g., Prevotella-enriched diets in Asia) or methodological variations in microbiota sequencing. Mechanistically, propionate (>500 μM) inhibits pituitary GH synthesis via GPR41/43-cAMP signaling, while butyrate enhances hepatic IGF-1 through GPR109A-mediated IL-6 secretion and osteoblastic histone deacetylase (HDAC) inhibition. Interventions such as probiotics (e.g., Lactobacillus plantarum increased IGF-1 by 1.2–1.8-fold in murine models) and high-fiber diets demonstrate preclinical efficacy but face clinical barriers, including poor adherence (<30%) and limited GHD-specific trials. Fecal microbiota transplantation (FMT) shows hormonal restoration in animal models but induces gastrointestinal adverse effects (22% bloating, 15% diarrhea) in humans. Multi-omics approaches are proposed to identify biomarkers (e.g., low butyrate + elevated trimethylamine N-oxide). These approaches also aim to optimize precision therapies, such as nanoparticle-delivered SCFAs. This review underscores the need for multicenter randomized controlled trials to validate synbiotics or engineered microbial consortia, bridging mechanistic insights into the microbiota-SCFA-endocrine axis with clinical translation for GHD management.